Homosexuality and Same Sex Prostitution in Criminology Studies (Law Research Review Quarterly, 2020)
Homosexuality is a behavior of social deviation that is considered to violate human nature and violate the norms that exist in Indonesia as a civilized country according to the First Precepts and Second Precepts. Ironically, there is no legal umbrella that can ensnare homosexuals, whereas if viewed from homosexual criminology this is included in crime because crime is not only considered as something that violates the rules contained in the legislation but something that is considered to violate the values values ​​and norms that exist in society that disturb security order and something that harms the community. From the point of view of criminology, as well as the legal arrangements governing LGBT if it is linked to the Criminal Code, and prevention and control efforts so that LGBT can be overcome. The method used in this study is a juridical approach, which is done by examining primary data by direct observation in the field. The factor behind a person being a part of homosexuals is environmental factors because the environment can lead someone in a negative or positive direction and if related to criminology according to my analysis can be related to Differential Association theory where crime can be learned through close communication. The legal regulation governing LGBT is still considered weak and if it is linked to the Criminal Code it cannot yet fully regulate LGBT because the elements in it have not been fulfilled and there is still a legal vacuum.